STRATEGI PEMBELAJARAN DIALOGIS DALAM PERSPEKTIF PAULO FREIRE SEBAGAI FONDASI PENDIDIKAN BERMUTU - Utubira, Everd Elseos Martin; Lakoruhut, Vicklan (Jurnal Kajian Pembelajaran dan Keilmuan, 2026)
This study aims to examine the relationship between the implementation of dialogic learning strategies and indicators of educational quality, as well as to analyze structural, cultural, and pedagogical constraints and contextual opportunities influencing their application in archipelagic regions. A qualitative approach was employed, with data collected through observation, in-depth interviews, and document analysis in several senior high schools in Tobelo, North Halmahera Regency. The findings reveal that dialogic learning practices have begun to emerge through reflective dialogue, collective knowledge construction, and more egalitarian pedagogical relationships between teachers and students. This approach contributes to improving the quality of the learning process by enhancing student engagement, fostering critical reflection, and increasing the relevance of learning to local socio-cultural contexts. However, its implementation remains constrained by the persistence of traditional teaching practices, limited pedagogical capacity among educators, and unequal distribution of educational resources in island regions. Based on these findings, the study highlights the need to develop a contextual and operational model of dialogic learning strategies at the senior high school level. Such a model should emphasize participatory pedagogical interaction while integrating cultural, social, and epistemological dimensions relevant to students’ local contexts. Key components include the development of a conceptual framework and instructional syntax, integration of local socio-cultural content, strengthening teachers’ competencies in dialogic pedagogy, promotion of collaborative learning, development of dialogic-based instructional materials, implementation of reflective and participatory assessment systems, and the creation of democratic and emancipatory learning environments.